Introduction: The Political Dynamics and Social Effects of Megaproject Development. Issue 5 (20th October 2018) - Bovensiepen, Judith; Meitzner Yoder, Laura S.
Abstract : This special issue examines the political context and social impacts of plans for two state-sponsored megaprojects in Timor-Leste: the Special Zone of Social Market Economy (ZEESM) in the Oecusse enclave, and the Tasi Mane Project stretching along the south coast. Tracing debates about national development models in Timor-Leste back to the Indonesian occupation and transition period to independence, this Introduction situates these projects within contemporary debates about development. We pay special attention to two key aspects: how megaprojects transform people's relations with the land, a vital source of livelihoods and cultural meaning; and how different ethnolinguistic groups in Timor-Leste are adapting local practice to accommodate change. We conclude by highlighting how megaprojects reflect and affect aspects of life beyond economic development: governance practice, assertion of sovereignty, sensory losses and identity, ritual adaptations and aspirations for the future.